2015
DOI: 10.1051/0004-6361/201525691
|View full text |Cite
|
Sign up to set email alerts
|

Parent population of flat-spectrum radio-loud narrow-line Seyfert 1 galaxies

Abstract: Flat-spectrum radio-loud narrow-line Seyfert 1 galaxies (NLS1s) are a recently discovered class of γ-ray emitting active galactic nuclei (AGN), that exhibit some blazar-like properties which are explained with the presence of a relativistic jet viewed at small angles. When blazars are observed at larger angles they appear as radio-galaxies, and we expect to observe an analogue parent population for beamed NLS1s. However, the number of known NLS1s with the jet viewed at large angles is not enough. Therefore, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(144 citation statements)
references
References 92 publications
(118 reference statements)
9
130
1
1
Order By: Relevance
“…Our results on the morphology and brightness temperature indicate that IRAS 17020+4544 is different from this sub-set of the NLS1 population; yet, it remains also markedly separated from the bulk of the radio quiet NLS1 population, which have much lower radio powers (as low as P 1.4 GHz ∼ 10 19 W Hz −1 ) and are seldom detected with VLBI (Giroletti & Panessa 2009;Doi et al 2013). One intriguing possibility is that IRAS 17020+4544 belongs to the elusive population of misaligned RL NLS1s (Berton et al 2015).…”
Section: Discussionmentioning
confidence: 70%
“…Our results on the morphology and brightness temperature indicate that IRAS 17020+4544 is different from this sub-set of the NLS1 population; yet, it remains also markedly separated from the bulk of the radio quiet NLS1 population, which have much lower radio powers (as low as P 1.4 GHz ∼ 10 19 W Hz −1 ) and are seldom detected with VLBI (Giroletti & Panessa 2009;Doi et al 2013). One intriguing possibility is that IRAS 17020+4544 belongs to the elusive population of misaligned RL NLS1s (Berton et al 2015).…”
Section: Discussionmentioning
confidence: 70%
“…Both paradigms are also discussed for γ-NLS1(e.g., Abdo et al 2009c;Foschini et al 2015;Berton et al 2015), and it has been proposed that CSS and RL-NLS1 are linked (e.g., Komossa et al 2006;Doi et al 2012;Caccianiga et al 2014;Komossa et al 2015;Gu et al 2015). Recently, Caccianiga et al (2015) have found evidence of significant star formation activity in a sample of RL-NLS1s, favouring the scenario that RL-NLS1s are young AGNs.…”
Section: Parsec-scale Structure and Jet Orientationmentioning
confidence: 99%
“…Then, Yuan et al (2008) compiled a genuine sample of 23 RL-NLS1s with RL 1.4 GHz > 100, with black hole masses of 10 6 -10 8 M and Eddingtion ratios R Edd ≈ 1. Based on these and other studies, Foschini et al (2015) and Berton et al (2015) have a combined sample of 60 sources with RL 5 GHz > 10. Only a few RL-NLS1s have been detected by Fermi/LAT (γ-NLS1, Abdo et al 2009b;Foschini et al 2015;D'Ammando et al 2015;Yao et al 2015, see Sect.…”
Section: Introductionmentioning
confidence: 95%
“…Our sample consists of 60 sources drawn from the papers by Foschini et al (2015) and Berton et al (2015), and it contains radio-quiet (but not radio-silent) NLS1s, F-NLS1s, and S-NLS1s. In this paper we report the detection of extended emission in one S-NLS1s, Mrk 783.…”
Section: Introductionmentioning
confidence: 99%